I, Emma Freke - Atkinson, E. J. (Elizabeth Jane), 1961- (Carolrhoda Books, 2010)
Growing up near Boston with her free-spirited mother and old-world grandfather, twelve-year-old Emma has always felt out of place but when she attends the family reunion her father's family holds annually in Wisconsin, she is in for some surprises.